2020
DOI: 10.1002/ppul.24994
|View full text |Cite
|
Sign up to set email alerts
|

Steam disinfection of toothbrushes from patients with cystic fibrosis: Evidence‐based recommendations

Abstract: Background: Patients with cystic fibrosis have increased morbidity/mortality due to chronic respiratory infections, which primarily originate from the environment. Infection prevention and control emphasize the importance of cleaning and disinfection of respiratory devices, however, there is a paucity of guidance on toothbrush hygiene, which have been shown to be a source of cystic fibrosis (CF) pathogens. Methods: This study examined steam disinfection of toothbrushes contaminated with clinically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Not only may these pathogens be present, but it has been recorded that poor oral hygiene procedures may induce cardiovascular disease since periodontal pathogens can infiltrate the circulatory system through injuries in the mouth [21]. Other chronic pathologies associated with poor oral hygiene include cystic fibrosis [22]. Also, it has been reported that some pathogens that colonize toothbrushes may express antimicrobial resistance genes, which can lead to health complications if those microorganisms infiltrate the circulatory system [23].…”
Section: Discussionmentioning
confidence: 99%
“…Not only may these pathogens be present, but it has been recorded that poor oral hygiene procedures may induce cardiovascular disease since periodontal pathogens can infiltrate the circulatory system through injuries in the mouth [21]. Other chronic pathologies associated with poor oral hygiene include cystic fibrosis [22]. Also, it has been reported that some pathogens that colonize toothbrushes may express antimicrobial resistance genes, which can lead to health complications if those microorganisms infiltrate the circulatory system [23].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, baby bottle steam disinfectors have only provided a steam disinfection cycle, which has left the disinfected items wet from the steam condensate created during the disinfection cycle. Steam disinfection has become popular both in hospital and with patients at home and is recommended for the disinfection of nebulizer devices in patients with cystic fibrosis (Bell et al, 2020) and for the disinfection of toothbrushes (Millar et al, 2020). More recently, steam disinfector devices have been produced to dry excess moisture from devices and fomites following disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…BB1022-GS; 220–240V; 50–60 Hz; 650W; Nuby UK Ltd. Tyne & Wear, UK) domestic steam disinfector-drier device was employed in this study. Thermal performance of this device has recently been described (Millar et al, 2021). The device consists of five components, namely, the base (containing in-built fans), main body, lower tray, upper tray, and lid.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Australian consensus guidelines stratified various activities and exposures by risk; a summary of high risk exposures are provided in Table 4[37 ▪▪ ]. Finally, new studies have demonstrated successful steam disinfection of household items such as toothbrushes and cookware [38,39]. These measures are targeted primarily toward families with multiple children with cystic fibrosis, in whom shared strains are common.…”
Section: Potential Role Of Infection Prevention and Control In Nonhea...mentioning
confidence: 99%